PENGARUH QUALITY CONTROL, SIKLUS PRODUKSI, DAN MANAJEMEN PERSEDIAAN BARANG JADI TERHADAP PENGENDALIAN INTERNAL DI PT. SAT NUSAPERSADA TBK - Augustine, Anggie Putri; Richmayati, Maya; Fadlilah, Andi Hidayatul (LPPM Universitas Putera Batam, 2025)
The urgency of this research lies in the importance of effective internal control in enhancing operational efficiency and reducing the risk of errors in production. This study employs a quantitative method using multiple regression analysis to examine the influence of each variable on internal control. The findings reveal that the Production Cycle has the most significant impact on internal control, followed by Quality Control and Finished Goods Inventory Management. The simultaneous test (F-test) also indicates that all three variables collectively have a significant effect on internal control. The coefficient of determination (R²) of 92.7% suggests that the research model is highly effective in explaining the variations in internal control. In conclusion, the Production Cycle, Quality Control, and Finished Goods Inventory Management significantly influence internal control at PT. Sat Nusapersada Tbk. Therefore, it is recommended that the company optimize the management of these three variables to improve operational efficiency and strengthen the existing internal control system. This study provides valuable insights for the company in addressing challenges in the increasingly competitive manufacturing industry.